Asas Kepastian Hukum atas Perkara Pengangkatan Anak di Pengadilan Agama - Ramli, Mohammad (Prodi HKI IAI Miftahul Ulum Pamekasan, 2024)
The Religious Court has the authority to examine, decide and resolve child adoption cases for people who are Muslim. This authority is regulated in Article 49 letter a number 20 of Law Number 3 of 2006 concerning Amendments to Law Number 7 concerning Religious Courts. In carrying out its authority, the Religious Court is based on the principle of Islamic personality, so ideally a person who is Muslim and wishes to apply for an adopted child should apply to the Religious Court. However, in reality the majority, including Muslims, submitted their petition to the District Court. The problem is, the District Court in deciding cases regarding applications for adopted children is based on customary law or Western law (BW), which in fact is different from Islamic law. The implications of adopting a child through the District Court will give rise to problems in the future, especially in inheritance issues, for example disputes between adopted children and other heirs.